2019
DOI: 10.17549/gbfr.2019.24.3.29
|View full text |Cite
|
Sign up to set email alerts
|

Inspecting the Relationship among E-service Quality, E-trust, E-customer Satisfaction and Behavioral Intentions of Online Shopping Customers

Abstract: A B S T R A C TThe purpose of this study is to clarify whether there are relationships among the four key factors contributing to the success of e-business: e-service quality, e-trust e-customer satisfaction and behavioral intentions, thus make a conclusion and provide better understanding in the field of e-service and e-marketing. This study method used to evaluate and test the scale and theoretical model in the study is quantitative research with sample size N = 476 through the survey to deliver questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0
7

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 26 publications
8
42
0
7
Order By: Relevance
“…The results of this research are also in accordance with research conducted (Dat and Vu, 2019;Rita, Oliveira and Farisa, 2019;and Al-dweeri, et al, 2017) where they found that e-service quality has an influence on e-trust in the environment virtual. E-service quality is important in increasing e-trust in online business (Rita, Oliveira and Farisa, 2019).…”
Section: Effect Of E-service Quality On E-loyaltysupporting
confidence: 89%
“…The results of this research are also in accordance with research conducted (Dat and Vu, 2019;Rita, Oliveira and Farisa, 2019;and Al-dweeri, et al, 2017) where they found that e-service quality has an influence on e-trust in the environment virtual. E-service quality is important in increasing e-trust in online business (Rita, Oliveira and Farisa, 2019).…”
Section: Effect Of E-service Quality On E-loyaltysupporting
confidence: 89%
“…In Vietnam, the banking sector has been considered as an important engine to promote the development of financial system and well perform of the economic growth at roughly 7 per cent since political and economic reforms since 1986 (V.C. Nguyen & Do, 2020;Tran & Foroudi, 2020;Tran & Quang, 2019). However, the profit in the banking sector remarkably decreased in 2012-2015 period because of bad debts in lending and economic depression.…”
Section: Introductionmentioning
confidence: 99%
“…Sedangkan menurut (Pratiwi et al, 2020) hasil penelitian menunjukan bahwa eservice dapat berpengaruh secara positif dan signifikan terhadap kepuasan pelanggan. artinya semakin tinggi kualitas e-service maka semakin tinggi tingkat loyalitas pelanggan.dan hasil penelitian menurut (Tran & Vu, 2019) hasil penelitiannya menyatakan bahwa studi ini telah menemukan dampak tidak langsung dan positif baru dari kualitas layanan elektronik pada perilaku niat melalui mediator e-trust dan e-customer satisfaction.…”
Section: Pendahuluanunclassified